Physical and Sociodemographic Features Associated With Quality of Life in Transgender Individuals Using Gender-Affirming Hormone Therapy - Da Silva, Eliane Dias (J Endocr Soc, 2021)
Background: Gender dysphoria is defined as a feeling of distress resulting from the incongruence between the gender assigned at birth and the identity gender and lasting longer than 6 months. In individuals with gender dysphoria, gender-affirming hormone therapy(GAHT) may improve quality of life (QoL). Objectives: Here, we aimed to assess perceived QoL and possible contributing factors in a sample of transgender women and transgender men using GAHT. Methods: In this cross-sectional study, transgender women and men were recruited by availability sampling from a national transgender health service. Individuals over 18 years old with a confirmed diagnosis of gender dysphoria receiving medically prescribed GAHT for at least 6 months were consecutively included. Also included were trans men who had undergone mastectomy and trans women who had received breast augmentation surgery. Individuals who had undergone gender affirmation surgery (specifically genital surgery) or with uncontrolled clinical/psychiatric conditions at the time of the initial assessment were excluded. Sociodemographic, physical, and hormone data were collected from all participants. The WHOQOL-BREF questionnaire was used to evaluate QoL. A total of 135 transgender individuals were invited. Seventeen individuals with previous genital surgery (12.6%) and five who refused to participate (3.7%) were excluded. Therefore, 113 patients were enrolled in the study (60 trans women and 53 trans men). Results: There was no significant difference in QoLbetween the groups. In trans women, greater breast development and stable relationships, and higher body mass index were associated with higher QoLdomain scores. In trans men, higher domain scores were found in individuals with a stable relationship, increased body hair, physical activity practice, and being employed. Conclusion: Data from this study suggest that GAHT-related physical characteristics are associated with higher QoLscores, and that sociodemographic parameters may impact these associations. Healthcare providers might consider these factors when planning interventions to improve QoLin transgender individuals.